Influence of wave group characteristics on loads in severe seas - Clauss, Günther F.; Dudek, Matthias; Klein, Marco (Volume 2: Structures, Safety and Reliability, 2011)
The precise knowledge of loads and motions in extreme sea states is indispensable to ensure reliability and survival of ships and floating offshore structures. In the last decades, several accidents in severe weather with disastrous consequences have shown the need for further investigations. Besides the sea state behavior and the local structural loads, one key parameter for safe ship design is the vertical bending moment. Previous investigations revealed that different ship design criteria, such as bow geometry and wave board height, affect the global loads significantly. Investigations in regular waves as well as in single high waves of vessels with different bow flares and freeboard heights show that the vertical bending moment increases significantly with increasing bow flare and freeboard height. Furthermore it became apparent that critical loads and motions do not have to come along with the highest wave which results in the main question of this paper: What is the worst case scenario - the highest rogue wave or a wave group with certain frequency characteristics? Which sea states have to be taken into account for the experimental evaluation of limiting criteria? This paper presents investigations in different critical wave sequences, i.e. two real-sea registrations accompanied by results in regular waves to evaluate the influence of the encountering wave characteristics on the vertical bending moment. For the model tests in the seakeeping basin of the Technical University Berlin a segmented RoRo vessel with large bow flare has been built at a scale of 1:70 and equipped with force transducers. The paper proves that critical loads and motions depend most notably on combinations of wave height, wave group sequences, crest steepness, encountering speed and the ships target position: Even small wave heights with unfavorable wave lengths can cause a critical situation.